Spiritual Treasure In "The Essays Or Counsels, Civil And Moral" Of Francis Bacon (Czech Journal of Multidisciplinary Innovations, 2024)
The famous English philosopher, statesman and thinker Francis Bacon is an author who made a great contribution to the development of the essay genre in the literature and philosophy of the European Renaissance. His book "The Essays or Counsels, Civil and Moral" (1625) is considered one of the valuable and rare works of not only of English but the world literature. This article is dedicated to the study of the unique thoughts expressed by the great English thinker in this literary source, and the author tried to convey to the reader his personal feelings as to the philosophical and moral thoughts expressed in the work concerning the inner worldview of the English thinker in the process of translating of the 15 essays of Francis Bacon directly from the original version into Uzbek language